Cleft Palate as Distinguishing Feature in a Patient with GABRB3 Epileptic Encephalopathy - Bamborschke, Daniel; Pergande, Matthias; Daimagüler, Hülya Sevcan; Mangold, Elisabeth; Dötsch, Jörg; Herkenrath, Peter; Cirak, Sebahattin; Fazeli, Walid (Neuropediatrics, 2019)
Mutations in GABAA-receptor subunit genes are associated with a heterogeneous spectrum of epilepsies. Patients with epilepsy caused by mutations in a specific GABAA-receptor (GABRA3) occasionally present with orofacial dysmorphism (e.g., cleft palates). While cleft palates have been described in Gabrb3 knockout mice and in humans with GABRB3 variants without epilepsy, the specific combination of epilepsy and cleft palate in humans with GABRB3 mutations has not yet been reported.We describe a patient with epileptic encephalopathy (EE) who presented with therapy-refractory neonatal-onset myoclonic seizures and severe developmental delay. Electroencephalogram showed burst suppression pattern at neonatal age and hypsarrhythmia at infantile age. Initial magnetic resonance imaging was unremarkable. As he additionally presented with a cleft palate, we were curious whether cleft palate and EE had the same genetic origin. Whole exome sequencing of the index patient revealed a novel pathogenic heterozygous de novo mutation in GABRB3 (c.899T > C; p.I300T). In consistency with Gabrb3 knockout mice data, this is the first report of cleft palate in a patient with GABRB3 associated EE.We suggest to add cleft palate to the phenotypic GABRB3 spectrum and to screen for mutations in GABAA-receptors in patients with EE and orofacial dysmorphism.
Keywords: GABRB3; GABAA-receptor; epilepsy; cleft palate